Effect of a Short Training Course on Empathy level in Medical Students: A Quasi-Experimental Study - Abdolhussein Shakurnia; Mahmood Maniati; Nasrin Khajeali; Maryam Barani (Kerman University of Medical Sciences, 2021)
Background: Empathy is an important component of effective communication of a patientpractitioner relationship. Medical students are expected to know this ability as part of their education.Objectives: This study aimed to assess the effect of a short-training course on the empathy levels of medical students.Methods: This is a quasi-experimental study conducted on eighty second-year medical students in Ahvaz Jundishapur University of Medical Sciences (AJUMS), Iran, 2019. The intervention comprised of a lecture-based short training course, which was taught by a psychiatrist and was held in two sessions (Two hours each) for two consecutive weeks. Empathy was assessed using the Jefferson Scale of Empathy-Student version (JSE) before and after the intervention. Students with empathy scores higher than average were considered high empathy group, and those with scores lower than average as low empathy group. Data were analyzed using paired T-tests through SPSS software, version 16.Results: The mean JSE score was 99.66±13.4 and 101.62 ± 16.37, before and after the -intervention, respectively. However, despite the score increased, the difference was not statistically significant (p=0.054). Nevertheless, the empathy scores of high-empathy students significantly increased after the-intervention (110.49 Vs 114.15, p=0.002). The empathy level also showed a significant enhancement in female students after training (p=0.006).Conclusion: This study shows that a short training course is somewhat effective in developing medical student empathy. The findings suggest a need for revision of content and implementation of this course training into the existing medical curriculum.